Efficacy and Outcomes of Posterior Inferior Cerebellar Artery (PICA) Bypass for Proximal PICA and Vertebral Artery-PICA Aneurysms: A Case Series. Issue 4 (16th February 2018) - Rennert, Robert C; Strickland, Ben A; Ravina, Kristine; Bakhsheshian, Joshua; Fredrickson, Vance; Tenser, Matthew; Amar, Arun; Mack, William; Carey, Joseph; Russin, Jonathan J
Abstract: BACKGROUND: Nonsaccular vertebral artery (VA) and posterior inferior cerebellar artery (PICA) aneurysms have high morbidity and mortality rates and are difficult to treat using standard microsurgical or endovascular techniques. Definitive revascularization can require clip trapping and/or vessel sacrifice, with PICA bypass. The published surgical experience with these approaches is limited. We herein review our recent surgical experience with PICA revascularization for complex PICA and VA/PICA aneurysms. OBJECTIVE: To determine the efficacy and outcomes of PICA bypass for revascularization of nonsaccular PICA and VA/PICA aneurysms. METHODS: Retrospective analysis of an institutional review board-approved, prospective database was performed to identify patients with PICA and VA/PICA aneurysms treated with PICA bypass at a single institution. Demographic information, aneurysm characteristics, temporary clip time, and neurological outcomes were recorded. RESULTS: Ten cases of PICA revascularization were performed for both ruptured (n = 8) and unruptured (n = 2) nonsaccular proximal PICA or VA/PICA aneurysms. Seven cases were performed without vessel grafts; 3 cases required harvest of the descending branch of the lateral femoral circumflex artery. Mean temporary clip time was 38 min (range 27-50 min). Good outcomes (Glasgow Outcomes Scale score of 5) were achieved in 70% (n = 7) of patients at time of discharge; the remaining patients had a Glasgow Outcomes Scale of 3. Two bypass-related complications occurred in this series; a hematoma at the graft harvest site requiring evacuation, and severe bypass graft spasm requiring multiple endovascular treatments. CONCLUSION: PICA bypass can be a safe, effective, and highly customizable tool for the revascularization of patients with nonsaccular proximal PICA and VA/PICA aneurysms.